Closed-Set Speech Discrimination Tests for Assessing Young Children. Issue 1 (January 2018) - Vickers, Deborah A.; Moore, Brian C. J.; Majeed, Arooj; Stephenson, Natalie; Alferaih, Hala; Baer, Thomas; Marriage, Josephine E.
Abstract : Objective: The main objective of this study is to obtain data assessing normative scores, test–retest reliability, critical differences, and the effect of age for two closed-set consonant-discrimination tests. Design: The two tests are intended for use with children aged 2 to 8 years. The tests were evaluated using normal-hearing children within the appropriate age range. The tests were (1) the closed-set consonant confusion test (CCT) and (2) the consonant-discrimination subtest of the closed-set Chear Auditory Perception Test (CAPT). Both were word-identification tests using stimuli presented at a low fixed level, chosen to avoid ceiling effects while avoiding the use of background noise. Each test was administered twice. Results: All children in the age range 3 years 2 months to 8 years 11 months gave meaningful scores and were able to respond reliably using a computer mouse or a touch screen to select one of four response options displayed on a screen for each trial. Assessment of test–retest reliability showed strong agreement between the two test runs (interclass correlation ≥ 0.8 for both tests). The critical differences were similar to those for other monosyllabic speech tests. Tables of these differences for the CCT and CAPT are provided for clinical use of the measures. Performance tended to improve with increasing age, especially for the CCT. Regression equations relating mean performance to age are given. Conclusions: The CCT is appropriate for children with developmental age in the range 2 to 4.5 years and the CAPT is appropriate as a follow-on test from the CCT. If a child scores 80% or more on the CCT, they can be further tested using the CAPT, which contains more advanced vocabulary and more difficult contrasts. This allows the assessment of consonant perception ability and of changes over time or after an intervention.